IbM PENGEMBANGAN POTENSI LOKAL POSDAYA DURIAN JAYA MENUJU DESA WISATA DI KELURAHAN BUBAKAN, KEC. MIJEN, KOTA SEMARANG - Rasiman .; Sudargo .; Mei Sulistyaningsih; Fenny Roshayati; Arri Handayani; Muniroh Munawar (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract ?é?á Based on the data analysis of monograph in Bubakan Village, whichhas various kinds of?é?á potential local resources (e.q:fruits, plants vegetable and cattle), Posdaya Durian Jayaas a partner of IbM, has some potential activities that can be developed?é?á as pioneer of potential local tourist resort intheareaofBubakanvillage. The present activities of the Posdaya are divided into several fields:a.Education;b.Health;c.Entrepreneurship; andd.Environment Care. Those localpotentialresources were still needed serious managerial development in accordance todesign a new local tourist resort. The IbM activities in RW02 Bubakan aimed at 1) making cat fish abon and various food from flourmocaf, 2) conducting a seminar with village officials, community leaders, and the group Posdaya to design a?é?á tourist village. 3) socializing about?é?á nutrients forchildren in Posyandu ?óÔé¼?ôMawar Dua?óÔé¼?Ø. Keyword: local potential resources, Posdaya Durian Jaya, local tourist resort